Forensic entomotoxicology: Current concepts, trends and challenges. (October 2019) - Chophi, Rito; Sharma, Spriha; Sharma, Sahil; Singh, Rajinder
Abstract: The application of forensic entomotoxicology in investigations of death by poisoning has gained popularity as insects serves as an alternative specimen (evidence) when conventional toxicological samples have degraded or are no longer available. Successful detection, identification, and quantification of drugs and toxic substances from insects have been demonstrated through various research experiments. In the present review paper, role of insects as toxicological sample, its collection and preservation, analysis using various instrumental techniques, and trends in the use of analytical techniques have been discussed. Limitations hindering the growth of this field and the way forward for future studies have been highlighted. In addition, the effect of poisons on insects used for postmortem interval estimation has been described. Highlights: A comprehensive and critical review of forensic entomotoxicology. Collection, preservation and analysis of insect evidence. Toxic substances analyzed from insect evidence over the past years. Trends in the use of analytical techniques. Challenges and limitation of forensic entomotoxicology.